An analytical model for shape memory alloy fiber-reinforced composite thin-walled beam undergoing large deflection. (16th March 2015) - Ren, Yongsheng; Sun, Shuangshuang
The structural model of the thin-walled laminated beams with integral shape memory alloy active fibers and accounting for geometrically nonlinear is presented in this article. The structural modeling is split into two parts: a two-dimensional analysis over the cross section and a geometrically nonlinear analysis of a beam along the beam span. The variational asymptotic method is used to formulate the force–deformation relationship equations taking into account the presence of active shape memory alloy fibers distributed along the cross section of the beam. The geometrically nonlinear governing equations are derived using variational principle and based on the von Kármán-type nonlinear strain–displacement relations. The equations are then solved using Galerkin's method and an incremental Newton–Raphson method. The validation for the proposed model has been carried out by comparison of the present results with those available in the literature. The results show that significant extension, bending, and twisting coupled nonlinear deflections occur during the phase transformation due to shape memory alloy actuation. The effects of the volume fraction of the shape memory alloy fiber and ply angle are also addressed.